An in vitro study of antibacterial efficacy of salvadorapersica (miswak) extract against enterococcus faecalis - Che Rosli, Munirah; Shahdan, Intan Azura; Muhamad Halil, Mohd Haikal (USIM Press, 2022)
Salvadora persica is widely used in dental field to improve dental health and promote dental hygiene. Although sodium hypochlorite is highly recommended and regarded as the most effective irrigant in root canal treatment to eliminate bacteria, it can cause harm to patients manifested by severe pain, rapid swelling and also obstruct breathing airway. However, it is believed that the chemicalcomposition of Salvadora persica helps to treat and act as an antibacterial agent in root canal therapy. This study aims to obtain the crude compound from Salvadora persica by using the freeze drying method and to compare the antibacterial activity of theSalvadora persicaand sodium hypochlorite against Enterococcus faecalis in aerobic condition. Antibacterial activity results showed that 150 mg/ml of Salvadora persica give comparable effect with sodium hypochlorite against Enterococcus faecalis. It is believed that 60% of alcoholic Salvadorapersica extraction is an effective antimicrobial agent to beutilized as an irrigant in root canal treatment.